2020
DOI: 10.1002/jor.24614
|View full text |Cite
|
Sign up to set email alerts
|

Advanced decision‐making using patient‐reported outcome measures in total joint replacement

Abstract: Up to one‐third of total joint replacement (TJR) procedures may be performed inappropriately in a subset of patients who remain dissatisfied with their outcomes, stressing the importance of shared decision‐making. Patient‐reported outcome measures capture physical, emotional, and social aspects of health and wellbeing from the patient's perspective. Powerful computer systems capable of performing highly sophisticated analysis using different types of data, including patient‐derived data, such as patient‐report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…Another study found that presurgical pain was not related to post-surgical pain [26] indicating that more factors should be involved in the decision for surgical intervention. Most recently, shared decision-making has been studied to shift the focus away from clinical assessment and incorporate patient-reported outcomes measures such as pain, function, and quality of life in the determination of the appropriate timing of surgery [27]. This study did not assess the proportion of patients who were contemplating surgery though not yet planned or the portion that accept the physician's recommendation for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that presurgical pain was not related to post-surgical pain [26] indicating that more factors should be involved in the decision for surgical intervention. Most recently, shared decision-making has been studied to shift the focus away from clinical assessment and incorporate patient-reported outcomes measures such as pain, function, and quality of life in the determination of the appropriate timing of surgery [27]. This study did not assess the proportion of patients who were contemplating surgery though not yet planned or the portion that accept the physician's recommendation for surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 37 Promising work in artificial intelligence can enhance decision making with generated personalized predictions using prior patient reported outcome measures, patient clinical risk factors, and psychosocial risk factors (depression, patient activation). 38 - 40 Personalized predictions provide an additional metric to engage patients, and guide discussions about surgical appropriateness and postoperative expectations. Importantly, engagement methods focused on decision making can be introduced into the clinical setting without impacting efficiency of the office visits, which benefits all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced algorithms offer an avenue to learn and adapt to different datasets including those relating to a patient's physical and psychosocial health and well-being from different populations and practices. Highly sophisticated analysis of a wide range of data is capable of generating impactful metrics that can be used to aid in better decision-making processes [73]. Jayakumar et al conducted a Purnomo et al Arthroplasty (2021) 3:37 randomized clinical trial of 129 patients with knee pain associated with OA.…”
Section: Clinical Decision Making and Future Directionsmentioning
confidence: 99%